Application of Distribute File System ＆ MPP Database Mashup Architecture in Telecom Big Data Platform - Yu Zhang; Xin Cai; Aimin Li; Yi Liu; Xiaohui Yao (Dianxin kexue)
Distributed file system and MPP database are two important directions in the domain of big data. Based on the research of the two techniques, the sketch and implement method of big data platform architecture planning and design were put forward using the mashup architecture, and the actual verification in the specific project was carried out. This architecture can combines the advantages of both two techniques, and can adapt to the different scenes of big data storage ＆ processing requirements.